Theory of Cryptography : 10th Theory of Cryptography Conference, TCC 2013, Tokyo, Japan, March 3-6, 2013. Proceedings - Sahai Amit (Lecture notes in computer science, 2013)
This book constitutes the thoroughly refereed proceedings of the 10th Theory of Cryptography Conference, TCC 2013, held in Tokyo, Japan, in March 2013. The 36 revised full papers presented were carefully reviewed and selected from 98 submissions. The papers cover topics such as study of known paradigms, approaches, and techniques, directed towards their better understanding and utilization; discovery of new paradigms, approaches and techniques that overcome limitations of the existing ones; formulation and treatment of new cryptographic problems; study of notions of security and relations among them; modeling and analysis of cryptographic algorithms; and study of the complexity assumptions used in cryptography.